2021
DOI: 10.1111/nmo.14249
|View full text |Cite
|
Sign up to set email alerts
|

Integrative effects of transcutaneous electrical acustimulation on abdominal pain, gastrointestinal motility, and inflammation in patients with early‐stage acute pancreatitis

Abstract: Background/Aims Gastrointestinal (GI) dysmotility in acute pancreatitis (AP) aggravates inflammation and results in severe complications. This study aimed to explore effects and possible mechanisms of transcutaneous electrical acustimulation (TEA) on abdominal pain, GI dysmotility, and inflammation in AP patients. Methods Forty‐two AP patients were blindly randomized to receive TEA (n = 21) at acupoints PC6 and ST36 or Sham‐TEA (n = 21) at sham points for 2 days. Symptom scores, gastric slow waves, autonomic f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…For example, a recent study found that, compared to sham-TEA, TEA at acupoints ST-36 and PC-6 improved abdominal pain (in addition to gastric motility and autonomic function) when applied in patients with early-stage acute pancreatitis. 37 In another study, TEA improved abdominal pain by 50% when applied in postoperative setting in patients recovering from surgery for gastrointestinal cancers. 38 The current study adds to this body of literature, specific to TEA, and provides refinement on the optimal TEA application methodology.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…For example, a recent study found that, compared to sham-TEA, TEA at acupoints ST-36 and PC-6 improved abdominal pain (in addition to gastric motility and autonomic function) when applied in patients with early-stage acute pancreatitis. 37 In another study, TEA improved abdominal pain by 50% when applied in postoperative setting in patients recovering from surgery for gastrointestinal cancers. 38 The current study adds to this body of literature, specific to TEA, and provides refinement on the optimal TEA application methodology.…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, TEA was found effective in other conditions characterized by abdominal pain. For example, a recent study found that, compared to sham‐TEA, TEA at acupoints ST‐36 and PC‐6 improved abdominal pain (in addition to gastric motility and autonomic function) when applied in patients with early‐stage acute pancreatitis 37 . In another study, TEA improved abdominal pain by 50% when applied in postoperative setting in patients recovering from surgery for gastrointestinal cancers 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Spontaneous defection is usually an indicator for starting EN in clinical practice and is widely used in researches on gastrointestinal obstruction [31][32][33]. One [34] research investigating transcutaneous electrical acustimulation for treating acute pancreatitis used first defection time as an important endpoint. In this study, we choose the first defection time as our primary outcome.…”
Section: Background and Rationale {6a}mentioning
confidence: 99%
“…Injury or inflammation can lead to persistent peripheral input and sensitization. [24] The lowgrade inflammatory is considered as the important pathogenesis of FD. That acute infections, food antigens, acid, and capsaicin can alter the steady state of the gastrointestinal tract and lead to dysfunction of the intestinal epithelial barrier, increasing mucosal permeability.…”
Section: The Avns Regulated Facilitatory Mediators Of the Inflammatio...mentioning
confidence: 99%
“…[25][26][27] Proinflammatory cytokines, chemokines, biogenic amines, bradykinins, prostaglandins, SP and several neurosurgeons are among the facilitatory mediators of the inflammation. [24] It has been demonstrated that SP and its neurokinin-1 receptor play a significant role in nociceptive perception that contributes to visceral hypersensitivity. [28] Yin et al found that visceral pain from irritable bowel syndrome can be relieved via mechanisms involving downregulation of SP in rats.…”
Section: The Avns Regulated Facilitatory Mediators Of the Inflammatio...mentioning
confidence: 99%